Isotopic methods for non‐destructive assessment of carbon dynamics in shrublands under long‐term climate change manipulation. Issue 4 (7th February 2018) - Andresen, Louise C.; Domínguez, Maria T.; Reinsch, Sabine; Smith, Andrew R.; Schmidt, Inger K.; Ambus, Per; Beier, Claus; Boeckx, Pascal; Bol, Roland; de Dato, Giovanbattista; Emmett, Bridget A.; Estiarte, Marc; et al.
Abstract: Long‐term climate change experiments are extremely valuable for studying ecosystem responses to environmental change. Examination of the vegetation and the soil should be non‐destructive to guarantee long‐term research. In this paper, we review field methods using isotope techniques for assessing carbon dynamics in the plant–soil–air continuum, based on recent field experience and examples from a European climate change manipulation network. Eight European semi‐natural shrubland ecosystems were exposed to warming and drought manipulations. One field site was additionally exposed to elevated atmospheric CO2 . We discuss the isotope methods that were used across the network to evaluate carbon fluxes and ecosystem responses, including: (1) analysis of the naturally rare isotopes of carbon ( 13 C and 14 C) and nitrogen ( 15 N); (2) use of in situ pulse labelling with 13 CO2, soil injections of 13 C‐ and 15 N‐enriched substrates, or continuous labelling by free air carbon dioxide enrichment (FACE) and (3) manipulation of isotopic composition of soil substrates ( 14 C) in laboratory‐based studies. The natural 14 C signature of soil respiration gave insight into a possible long‐term shift in the partitioning between the decomposition of young and old soil carbon sources. Contrastingly, the stable isotopes 13 C and 15 N were used for shorter‐term processes, as the residence time in a certain compartment of the stable isotope label signal is limited. The use of labelled carbon‐compounds to study carbon mineralisation by soil micro‐organisms enabled to determine the long‐term effect of climate change on microbial carbon uptake kinetics and turnover. Based on the experience with the experimental work, we provide recommendations for the application of the reviewed methods to study carbon fluxes in the plant–soil–air continuum in climate change experiments. 13 C‐labelling techniques exert minimal physical disturbances, however, the dilution of the applied isotopic signal can be challenging. In addition, the contamination of the field site with excess 13 C or 14 C can be a problem for subsequent natural abundance ( 14 C and 13 C) or label studies. The use of slight changes in carbon and nitrogen natural abundance does not present problems related to potential dilution or contamination risks, but the usefulness depends on the fractionation rate of the studied processes.